Treatment outcomes of pars plana vitrectomy-hyaloidotomy-zonulectomy-iridectomy in malignant glaucoma in a tertiary eye care center in South India - Mrunali M Dhavalikar; M Manju; Ganesh V Raman; Premanand Chandran; Prema Subramaniam (Indian Journal of Ophthalmology)
Purpose: To report the clinical profile and treatment outcomes of malignant glaucoma and the efficacy of pars plana vitrectomy-hyaloidotomy-zonulectomy and iridectomy in Indian eyes. Design: Retrospective observational study. Methods: The study was a retrospective chart review. Medical records of patients diagnosed with malignant glaucoma between December 2018 and August 2022 were reviewed. Patients with the diagnosis of malignant glaucoma and those who underwent pars plana vitrectomy-hyaloidotomy-zonulectomy-iridectomy were included in the study. Patients with less than 3 months of follow-up were excluded from the study. Data collected included demographic data, primary ocular procedure, best-corrected visual acuity in logMAR, and lens status. The data also included intraocular pressure and number of antiglaucoma medications used at the time of presentation and during follow-ups. Results: The final analysis included 36 eyes of 30 patients. There was a statistically significant reduction of intraocular pressure at each visit (P value = 0.001) and in the number of antiglaucoma medications (P value < 0.001). A total of 29 eyes had a follow-up of 6 months, 19 eyes (65.5%) had a complete success, and 10 eyes (34.4%) had qualified success at the end of 6 months. Conclusion: Pars plana vitrectomy-hyaloidotomy-zonulectomy-iridectomy surgery has favorable outcomes in eyes with malignant glaucoma.